Molybdenum Imido Alkylidene Metathesis Catalysts that Contain Electron Withdrawing Biphenolates or Binaphtholates - Singh, Rojendra (2007)
We have prepared new Mo(NR)(CHCMe(2)Ph)(diolate) complexes (R = 2,6-i-Pr(2)C(6)H(3), 2,6-Me(2)C(6)H(3), 1-Adamantyl, or 2-CF(3)C(6)H(4)) that contain relatively electron-withdrawing binaphtholate (3,3′-bis-(9-anthracenyl), 3,3′-bispentafluorophenyl, or 3,3′-bis(3,5-bis(trifluoromethyl)phenyl) or biphenolate (3,3′-di-tert-butyl-5,5′-bistrifluoromethyl-6,6′-dimethyl-1,1′-biphenyl-2,2′-diolate) ligands. We also have prepared new monomeric Mo(NR)(CHCMe(2)Ph)(2,5-dimethylpyrrolide)(2) complexes and have treated them with biphenols or binaphthols in order to prepare several Mo(NR)(CHCMe(2)Ph)(diolate) species. In one case the new Mo(NR)(CHCMe(2)Ph)(diolate) complexes could be prepared only through reaction of a binaphthol [3,3′-bis(pentafluorophenyl)binaphthol] with a bis(2,5-dimethylpyrrolide) complex. The pyrrolide approach can be employed either to isolate catalysts on a preparative scale or to generate catalysts in situ. Several simple preliminary ring-closing metathesis reactions show that the new complexes are catalytically competent.